2014
DOI: 10.1016/j.jcyt.2014.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell–based biological pacemakers from proof of principle to therapy: a review

Abstract: Electronic pacemakers are the standard therapy for bradycardia related symptoms but have shortcomings. Over the past 15 years experimental evidence has demonstrated that gene and cell-based therapies can create a biological pacemaker. Recently, physiologically acceptable rates have been reported with an adenovirus-based approach. But adenovirus-based protein expression does not last more than 4 weeks, which limits its clinical applicability. Cell-based platforms are potential candidates for longer expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 64 publications
0
20
0
1
Order By: Relevance
“…Several attempts have shown that in situ delivery of funny channels to defective cardiac muscle by gene-or cell-based methods can be employed in the attempt to develop biological pacemakers, with the aim to replace electronic devices. Exhaustive review work covers this important subject (Robinson et al, 2006;Rosen et al, 2011;Chauveau et al, 2014).…”
Section: Practical Applications Of the Functional Properties Of Funnymentioning
confidence: 99%
“…Several attempts have shown that in situ delivery of funny channels to defective cardiac muscle by gene-or cell-based methods can be employed in the attempt to develop biological pacemakers, with the aim to replace electronic devices. Exhaustive review work covers this important subject (Robinson et al, 2006;Rosen et al, 2011;Chauveau et al, 2014).…”
Section: Practical Applications Of the Functional Properties Of Funnymentioning
confidence: 99%
“…The SA node is the pacemaker of the heart, responsible for initiation of the heartbeat and the branching Purkinje fibers ensure that impulses are rapidly conducted throughout the heart to synchronize contraction and optimize ejection fraction. Life-threatening arrhythmias resulting from dysfunctional pacing have been revolutionized by electronic pacemakers but their reliance on batteries and electronic control systems highlight potential advantages of biological or bio-electronic tandem approaches to cardiac pacing [76, 77], including genetic engineering [78] and cell implantation [79]. The recent advent of cardiac optogenetics, where transgenic expression of light-gated ion channels permits optical control of cardiac pacing [80, 81] and termination of reentrant electrical activation [82] (e.g., spiral waves), suggests that gene and cell delivery methods can be used to impart light sensitivity on cardiac tissues for - low-energy pacing of target cells [83].…”
Section: Design Criteria For Engineered Cardiac Tissuesmentioning
confidence: 99%
“…When the apparent mechanisms summarized in Table 1 are put together with the calcium channel blocker studies and other studies on widespread changes in calcium fluxes and calcium signaling following microwave EMF exposures, we are left without any alternative, non-VGCC target of EMF action that currently can be studied for its role in producing biological effects in humans. (35) and can be derived from stem cells (79). Two approaches suggest themselves for measuring responses of such cells to EMF exposure: Cells in culture could be monitored for NO production using an NO electrode in the gas phase over the culture, both before and following EMF exposure.…”
Section: Reported Biologic Response Apparent Mechanism(s) Citation(s)mentioning
confidence: 99%